Pengembangan Buku Cerita Berbasis Kearifan Lokal Untuk Meningkatkan Kreativitas Anak Usia Dini - Dwi Lyna Sari; Dwi Ismawati; Lazfihma; Meli Afrodita (JURNAL ARMADA PENDIDIKAN, 2026)
This study aims to develop a local wisdom–based children’s storybook entitled Bujang Awang Tabuang to enhance the creativity of Group B early childhood learners. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects involved 18 children in Group B. The validation results indicated that the storybook was categorized as highly feasible, with material expert validation reaching 85%, media expert validation 90%, and teacher evaluation 87%. The results of the limited field trial demonstrated an effectiveness rate of 89%. The novelty of this study lies in the systematic integration of Bengkulu local wisdom into the narrative structure, illustrations, and creativity-based pedagogical activities of the children’s storybook, which was empirically tested using early childhood creativity indicators. The findings confirm that local wisdom–based storybooks function not only as cultural literacy media but also as an effective strategy for creating contextual learning and stimulating creativity in early childhood education.